Implementation of the Islamization of Contemporary Knowledge (IOCK) at the Department of Islamic Economics, University of Darussalam Gontor, Indonesia - Nazia Dinia; Novan Fatchu Alafianta; Nurul Najwani binti Ghazali (Tasfiyah: Jurnal Pemikiran Islam, 2025)
This study aims to investigate the implementation of the Islamization of Contemporary Knowledge (IOCK) at the University of Darussalam Gontor, with a focus on the Department of Islamic Economics. The research employs qualitative methods, describing, comparing, and analysing the three pivotal aspects of science as outlined by Imre Lakatos and Thomas Kuhn: Hardcore (Worldview), Hypothesis (Paradigm), and a series of theories. The study aims to examine the implementation of these aspects at the BA levels of the Department of Islamic Economics. Undergraduate students are required to take courses on Islamic and Western worldviews and paradigms for seven semesters. Master's-level students take courses on the theory of worldview and IOCK as an Islamic paradigm, write papers and theses on Islamization, and PhD students conduct research on the practice of Islamization by collaborating with lecturers from different departments. The output of the Islamization program includes textbooks, articles for journals, and scientific works, such as seminar articles and field research Findings show that 67% of students perceive the IOCK program as tedious and repetitive, while 48% of lectures without an Islamic studies background struggle to grasp its theoretical concepts. To address these challenges, the study recommends structured inter-Department collaboration and targeted capacity-building programs for lecturers, ensuring that IOCK is taught more dynamically and understood across disciplines. Such measures are expected to increase student engagement and enhance the quality of integrative Islamization research.